2010
DOI: 10.1074/jbc.m109.077164
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Adipocyte Differentiation by Aldo-keto Reductase 1B3 Acting as Prostaglandin F2α Synthase

Abstract: Prostaglandin (PG) F 2␣ suppresses adipocyte differentiation by inhibiting the function of peroxisome proliferatoractivated receptor ␥. However, PGF 2␣ synthase (PGFS) in adipocytes remains to be identified. Here, we studied the expression of members of the aldo-keto reductase (AKR) 1B family acting as PGFS during adipogenesis of mouse 3T3-L1 cells. AKR1B3 mRNA was expressed in preadipocytes, and its level increased about 4-fold at day 1 after initiation of adipocyte differentiation, and then quickly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 36 publications
5
76
2
3
Order By: Relevance
“…Other studies have shown that butein inhibits aldo-keto reductase 1B family members, resulting in less prostaglandin F2 ␣ production ( 38,39 ). However, knockdown and pharmacological inhibition of aldo-keto reductase induces adipogenesis and PPAR ␥ expression ( 40 ). Thus, possible inhibition of aldo-keto reductase by butein may not account for its effects on adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies have shown that butein inhibits aldo-keto reductase 1B family members, resulting in less prostaglandin F2 ␣ production ( 38,39 ). However, knockdown and pharmacological inhibition of aldo-keto reductase induces adipogenesis and PPAR ␥ expression ( 40 ). Thus, possible inhibition of aldo-keto reductase by butein may not account for its effects on adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 73%
“…The level of PGF 2 ␣ rapidly increased to a peak 3 h after initiation of differentiation and then declined, indicating that PGF 2 ␣ suppresses in the early phase of adipogenesis ( 13 ). Knockdown of aldo-keto reductase 1B3 (AKR1B3), a PGFS, decreased de novo PGF 2 ␣ biosynthesis in 3T3-L1 cells and then further promoted lipid accumulation ( 13 ). It has been shown that PGF 2 ␣ suppressed adipogensis by enhancing phosphorylation of PPAR ␥ via prostaglandin F receptor-activated MEK⁄ERK cascade ( 14 ).…”
Section: Ptgr-3 Decreases Proadipogenic Effect Of 15-keto-pge 2 Throumentioning
confidence: 99%
“…Prostaglandin F 2 ␣ (PGF 2 ␣ ) is generated from PGH 2 by PGF 2 ␣ synthase (PGFS), and PGF 2 ␣ is reported to be an inhibitory modulator of adipocyte differentiation ( 12 ). The level of PGF 2 ␣ rapidly increased to a peak 3 h after initiation of differentiation and then declined, indicating that PGF 2 ␣ suppresses in the early phase of adipogenesis ( 13 ). Knockdown of aldo-keto reductase 1B3 (AKR1B3), a PGFS, decreased de novo PGF 2 ␣ biosynthesis in 3T3-L1 cells and then further promoted lipid accumulation ( 13 ).…”
Section: Ptgr-3 Decreases Proadipogenic Effect Of 15-keto-pge 2 Throumentioning
confidence: 99%
“…On day 2, the medium was replaced with DMEM containing insulin (10 g/ml) alone and changed every 2 days. Oil red O staining was carried out as described previously (8).…”
Section: Cell Culture Mouse Adipocytic 3t3-l1 Cells and Human Hela Cmentioning
confidence: 99%